Assessment of the Current Status of Water Management and Challenges: Implication to the Water Issues of the Irrigation Scheme, Community Fisheries and Community Fish Refuge - Kong, Heng; Sithirith, Mak; Kongkroy, Chay; Sok, Sao; De Silva, Sanjiv; Soth, Sobot; Thavrin, Tim; Keo, Tysor; Hok, Syha (WorldFish, 2024)
The study examines the water management systems and challenges faced by rice farmers in Kokoh and Beoung Sneh communes. With an average household size of five members, the main occupations of the residents revolve around rice farming, fishing, and labor. The majority rely on multiple water sources such as irrigation canals, rainfed systems, underground water, and lakes to sustain agricultural activities. However, increasing water demand for dry-season rice cultivation, combined with climate-induced stress, exacerbates water shortages, particularly during the peak dry months.